The Persistence of Antibodies in ESRD Patients 12 Months after the BNT162b2 Vaccine Booster Dose. - Ummu Afeera, Zainulabid; Mohammad Hanif, Hashim; Abdullah Shamsir, Abd Mokti; Awla, Mohd Azraai; Hajar Fauzan, Ahmad; Ahmad Mahfuz, Gazali (UniKL Royal College of Medicine Perak, 2024)
End-stage renal disease (ESRD) patients undergoing haemodialysis have been reported to have impaired humoral response after coronavirus disease 2019 vaccination. However, most studies focus on one antibody profile or one-time point only. Here, we longitudinally investigate the antibody response towards severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) in ESRD patients after receiving the primary BNT162b2 vaccine schedule and a booster dose. Neutralising antibodies against SARS-CoV-2 were detected after the first vaccine dose, which increased exponentially after the second vaccine dose, maintaining similar levels even after 12 months of the booster dose in all patients. Immunoglobulin G (IgG) but not immunoglobulin M against Spike protein and receptor binding domain were maintained 12 months after the booster dose, and correlation analyses confirmed the relationship between neutralising antibodies and IgG responses. In conclusion, neutralising and IgG antibodies persist in ESRD patients 12 months after the BNT126b2 booster dose, a novel study finding.